SPE Asia Pacific Oil and Gas Conference and Exhibition 2004
DOI: 10.2118/88486-ms
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Desorption of Oil from Oil-Based Drilling Fluids Cuttings: Processes and Technologies

Abstract: Proposal This paper presents the results of a study of processes and technologies for the thermal desorption of oil from oil-based drilling fluids cuttings for both onshore and offshore applications. A field investigation of available technologies designed to separate oil from oil-based drilling fluids cuttings by thermal desorption was conducted. In addition, some technologies that perform separation by physical-chemical means were also investigated; however, all commercial processes present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Reported management options for drill cuttings are expensive (e.g., slurry reinjection [12]); thermal desorption [13]; and incineration [14]), require intensive energy use (e.g., incineration and thermal or microwave desorption [15]), time consuming (e.g., biological methods such as bioremediation [16] and phytoremediation [17]), or environmentally unsustainable (e.g., disposal in landfills [18]; reuse in construction without prior treatment [19]). Recent studies [20,21] have also shown the possibility of using stabilization/solidification (S/S) with hydraulic binders as a possible treatment option, with the potential of using the stabilized/solidified (s/s) product for useful purposes.…”
Section: Drilling Fluids and Cuttingsmentioning
confidence: 99%
“…Reported management options for drill cuttings are expensive (e.g., slurry reinjection [12]); thermal desorption [13]; and incineration [14]), require intensive energy use (e.g., incineration and thermal or microwave desorption [15]), time consuming (e.g., biological methods such as bioremediation [16] and phytoremediation [17]), or environmentally unsustainable (e.g., disposal in landfills [18]; reuse in construction without prior treatment [19]). Recent studies [20,21] have also shown the possibility of using stabilization/solidification (S/S) with hydraulic binders as a possible treatment option, with the potential of using the stabilized/solidified (s/s) product for useful purposes.…”
Section: Drilling Fluids and Cuttingsmentioning
confidence: 99%
“…Additionally, local residents are often against storage of such hazardous waste in their neighborhood. The most applied option for treatment of oil contaminated waste is thermal desorption of organic compounds [4,5]. The thermal process can be conducted in cement kiln and, additionally, leachable inorganic residues can be immobilized by in situ formed mineral phases (for example hydroxyapatite) [6].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal desorption disposal of oily cuttings has attracted attention because of its advantages of high efficiency, less secondary pollution, strong adaptability of raw materials, and reusable of processed products (Jones et al 2002;Stephenson et al 2004;Júnior et al 2017). For on-site continuous processing, heating mode and material carrier are two important technical links of the thermal desorption unit (TDU).…”
Section: Introductionmentioning
confidence: 99%
“…Fixed bed and fluidized bed are typical installations (Schmidt and Kaminsky 2001;Shen and Zhang 2003;Liu et al 2008), which are generally considered suitable for laboratory research. Rotary barrel device (or rotary kiln) is an optional scheme for continuous processing of materials (Fortuna et al 1997;Chen et al 2006;Sun et al 2017). The rotary barrel device usually fixes up the heating unit on the outer side, heating the material through heat conduction.…”
Section: Introductionmentioning
confidence: 99%